ANALISIS FUNGSI PELAKSANAAN PENGAWASAN LALU LINTAS BARANG IMPOR OLEH DIREKTORAT JENDAR BEA CUKAI KOTA BATAM - Sakti, Wiranto Bima; Salsabila, Lubna (LPPM Universitas Putera Batam, 2024)
The research done by the Directorate General of Customs and Excise (DJBC) in Batam City focuses on the role, techniques, and challenges encountered in supervising imported commodities. The role of DJBC in Batam City is crucial since it oversees the importation of commodities, ensures adherence to customs procedures, and combats smuggling. The DJBC employs legal restrictions, such as the Customs Law, to oversee the transportation of imported products. Despite the use of monitoring techniques such as physical inspection and cross-border supervision by DJBC, there are still impediments that impede their effectiveness. Obstacles that arise include insufficient resources, limited public knowledge of import rules, and inadequate information concerning smuggling operations. The city of Batam's advantageous geographical position in close proximity to neighboring nations, including Singapore and Malaysia, further complicates the task of monitoring imported commodities. Enhancing public legal knowledge and ensuring sufficient resources can enhance DJBC's ability to effectively fulfill its supervisory responsibilities in safeguarding the interests of the state and society.